Conducting polymer/bio‐material composite coatings for corrosion protection. Issue 3 (13th November 2017) - Sambyal, Pradeep; Ruhi, Gazala; Mishra, Monu; Gupta, Govind; Dhawan, Sundeep K.
Abstract : Present study demonstrates a facile in situ oxidative copolymerization method to synthesize conducting copolymer composites in aqueous chitosan medium. The development of poly(aniline‐co‐o‐toluidine)–chitosan–SiO2 /epoxy composite coatings were carried out by thermal curing of the spray‐coated mild steel substrates. FT‐IR analysis, XRD studies, SEM and HR‐TEM evidenced that the composite has synergistically integrated properties of the copolymer and the SiO2 nanoparticles. The electrochemical analyses of the coatings in 3.5% NaCl solution manifest an efficient role of copolymer composite in the remarkable improvement of the corrosion resistance of the substrate. The analyses involve Tafel polarization and electrochemical impedance spectroscopy (EIS) studies. The corrosion inhibition property of conducting copolymers, the film forming ability of chitosan, and robustness of SiO2 nanoparticles kept the corrosion rate of the coatings significantly low, under highly corrosive conditions. Mild steel coated with 3.0% loading of copolymer composite coating demonstrated very low corrosion current density ( i corr ) and significantly high pore resistance ( R pore ). Abstract : Composite coatings of high corrosion resistance are developed by combining the unique properties of conducting copolymers {poly(aniline‐co‐o‐toluidine)}, chitosan and SiO2 nanoparticles. The electroactive property of the conducting polymer (metal surface passivation and recuperation of defects), the film forming tendency of chitosan and the SiO2 nanoparticles, as fillers, improve the mechanical integrity of the coating.